Rukhsah for Menstruating Women in the Interpretation of Ahkam Verses: A Comparative Study of Al-Qurthubi and Wahbah az-Zuhaili: (Rukhshah bagi Perempuan Haid dalam Perspektif Tafsir Ahkam: Studi Komparatif Kitab Al-Qurthubi dan Al-Munir Karya Wahbah Az-Zuhaili) - Karim, Dudung Abdul; Lestari, Puji; Mahdhor, Muslich Marzuki; Rosyid, Ayi Abdul (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study examines the concept of rukhsah (legal concession) for menstruating women as articulated in the Qur’an, through a comparative analysis of two prominent exegetical works: Al-Jamiʿ li Ahkam al-Qurʾan by Al-Qurthubi and Tafsir al-Munir by Wahbah az-Zuhaili. Employing a qualitative library research design and the tafsir muqaran approach formulated by ʿAbd al-Hayy al-Farmawi, the study identifies, collects, and interprets relevant Qur’anic verses addressing menstruation and legal dispensations. The findings reveal a shared recognition of certain ritual prohibitions—such as prayer, fasting, sexual intercourse, and tawaf—yet notable divergences emerge in their views on Qur’anic recitation, mosque entry, and ritual purity. Al-Qurthubi maintains a more restrictive legal stance grounded in classical fiqh, while az-Zuhaili offers a more contextualized interpretation informed by contemporary realities, including advances in hygiene and medical understanding. This study introduces a novel comparative hermeneutical framework that bridges traditional and modern perspectives, contributing to the discourse on gender-sensitive Qur’anic interpretation. It underscores the potential for a more inclusive and practical application of Islamic legal principles for menstruating women in the modern era.